Remanufacturing in automotive industry: Challenges and limitations - Paulina Golinska-Dawson; Arkadiusz Kawa (Journal of Industrial Engineering and Management (JIEM), 2011)
Purpose: The aim of this paper is to provide the framework for management of reverse flow of materials in automotive industry. The emphasis is placed on the remanufacturing activities. Materials management in such conditions is a real challenge. The cause for this is parallel use of raw materials and reused materials. Such hybrid flows of materials are characterized by increased level of uncertainty connected with amount, quality and timing. Design/methodology/approach: This paper presents a comprehensive review of remanufacturing and traditional manufacturing. The stabilization of reverse flows is crucial for continuity of remanufacturing operations. The simulation model and results are discussed regarding stabilization of the reverse flows. Findings: Authors identify main problems that appear in the area of combining at the production system forward and reverse flows of materials. The agent-based technology is applied for configuration and stabilization of reverse network. Research limitations/implications: Paper is case - oriented.Practical implications: Both logistician and IT researchers might benefit from authors approach. Originality/value: Authors provide an interdisciplinary approach combining operations management, logistics and information technology.
Keywords: 650; reverse logistics; remanufacturing; closed loop supply chain; simulation experiments